Pengaruh Etika Bisnis Terhadap Kepuasan Pelanggan Andayani Waroeng Steak N Djawa (Studi Pada Andayani Waroeng Steak N Djawa Di Pamekasan) - Berry Irsyad Al Amir (Jurnal Studi Manajemen dan Bisnis, 2018)
Business ethics is a code of conduct employers based on the value - moral values and norms are used as guidance in making decisions and solving problems Zimmerer (1996:20). Menurut Ronald J. Ebert dan Ricky M. Griffin (200:80) Business ethics is a term often used to indicate a person's ethical behavior of managers or employees of an organization.Satisfaction is of feeling happy or disappointed someone who comes from a comparison between the impression of the performance (or result) of a product and hopes (Ronny A. Rusly  (2002 :  37)This study aims to determine whether there is influence of the application of business ethics to customer satisfaction in Andayani Waroeng Steak N Java in Pamekasan. The sample collection technique using accidental sampling with analysis of data using multiple linear regression.